Examining medical-surgical nurse shift-to-shift handoffs to identify process, failures, and effects. Issue 2 (3rd April 2019) - Ernst, Katherine; McComb, Sara; Ley, Cathaleen
Abstract: This research examined medical-surgical nurse shift-to-shift handoffs to identify the generic handoff process steps, as well as failure modes and effects, to develop causal explanations linking handoff characteristics to subsequent nursing care activities. The study used failure mode and effects analysis as an analytic framework for conducting secondary analysis on an existing focus group dataset. The dataset included five transcripts of focus groups with medical-surgical nurses describing their ideal handoff, ways handoff went poorly and effects post-handoff. Authors examined dataset for preferred handoff process steps, failure modes, and effects. A detailed handoff process was identified, including pre and post-handoff activities for both incoming and outgoing nurses. Handoff failures may result in negative effects for the nurse during handoff, in transition to and when providing patient care. An early failure, where the incoming nurse does not read the patients' medical records before handoff, resulted in a cascade of effects which triggered later failures or exacerbated the effects of later failures. The analysis revealed individual effects with many causal factors; such causes are confounded using existing handoff measures. The study's results can be used as a handoff process model for validation, to develop improved handoff measures, and for designing handoff improvements.